Мonitoring the capacitor charge voltage in the pulse voltage generator using the accelerator of relativistic electron beams - Batrakov, A.B.; Glushko, E.G.; Zinchenko, A.A.; Lonin, Yu.F.; Ponomaryov, A.G.; Fedotov, S.I. (Вопросы атомной науки и техники, 2018)
Noise-protected high charge voltage meter was manufactured using terminal capacitors of the four-channel pulse voltage generator (PVG). The noise protection is provided by the use of communication lines with fiberoptic cables. This measuring device is successfully used for the relativistic electron beam (REB) accelerator «Temp-B» and it provides the measurement accuracy of ~ 0.5% in the electromagnetic noise environment.